Growth stimulation of two legumes (Vicia faba and Pisum sativum) using phosphate-solubilizing bacteria inoculation - Janati, Walid; Mikou, Karima; El Ghadraoui, Lahsen; Errachidi, Faouzi (Frontiers in Microbiology, 2023)
The application of chemical fertilizers for plant growth and protection is one of the reasons for the environment and ecosystem destruction, thus, sustainable agriculture is gaining popularity in research and among farming communities. Although most soils are high in total phosphorus (P), a large portion is unavailable to plants and regarded as a growth-limiting factor. P-solubilizing bacteria (PSB) exploitation is a newly developed bio-solution for enhancing rhizosphere P availability; however, the effect of these bacteria on soil quality and the different phases of plant growth remains unknown. This study aims to evaluate the impact of five strains of PSB, isolated from legume rhizosphere, on the growth of two plants (Vicia faba and Pisum sativum) and certain soil properties. The efficient strains of PSB used are characterized by the P-solubilization, the ACC deaminase activity, the fixation of N, and the IAA, HCN, and siderophores production. The activity of these bacteria is tested in vitro and in vivo under controlled conditions on the growth of the two plants supplemented with the rock P (RP). According to our findings, all PSBs strains outperformed the control in terms of enhancing the growth of the tested legumes with a percentage ranging from 77.78 to 88.88%, respectively. The results showed that all treatments significantly improved plant parameters like nitrogen- (N) and P-content in the plants (67.50, 23.11%), respectively. Also, an increase in the fresh and dry weights of above- (41.17, 38.57%) and below-ground biomasses (56.6, 42.28%), respectively. Compared to the control, this leads to an increase of 72% in root length, 40.91% in plant dry weight, and 40.07% in fresh weight. Rhizospheric soil in PSBs treatments displayed high levels of N, P, and organic matter. All treatments were found to have significantly higher levels of alkaline phosphatase, basal soil respiration, and β-glucosidase activity than the control. It is concluded that multi-traits PSB can be an alternative for utilizing chemical fertilizers to enhance soil quality and plant growth. Despite the potency of PSBs, its use as a source for the development of sustainable agriculture implies focusing on crop species and adaptation, stress tolerance and climate resilience.